Village Chicken Production and Marketing in West Gojjam Zone, Ethiopia - Assefa, Habtemariam; Bogale, Aklilu; Gebremedhin, Berhanu; Mekuriaw, Zeleke; Derso, Teshome; Dessalegn, Yigzaw; Tegegne, Azage; Hoekstra, Dirk (Current Research in Agricultural Sciences, 2016)
Chicken production in West Gojjam zone was characterized by using indigenous chicken with low input-output level. Despite its diverse socio economic role for smallholder farmers, production and productivity of village chicken was very low. As the result, chicken producers were not benefited from the sector. Therefore, this study was conducted with the aim of characterizing chicken rearing practice, flock dynamics and determining the off-take rate of village chicken production system. It was conducted in West Gojjam Zone of Ethiopia. Multi-stage sampling technique was used to select representative respondents. A total of 500 farmers were interviewed. In the study area, the average numbers of local and exotic chickens kept by smallholder producers were 8.44+0.42 and 0.49+0.10chicken, respectively with the overall mean 8.93+0.42chicken. The flock structure was highly dominated by young chicks (3.82+0.28) and hen (2.47+0.09). The average chicken migrated into the flock per household per annum was 10.32+ 0.80 birds, whereas the outflow from the flock was 16.62+0.85birds. The number of chicken was higher at the middle of the year than the beginning and end of the year. On average, 2.9+0.12 layer chickens were kept per household. From which, in average 307.2+ 20.2 eggs were produced from local and improved breed in a year. Marketing in the district and PA were important marketing places for egg and live birds with the off-take rate of 34.94%. To improve chicken production in the study area, adaptive improved chicken breed should be introduced. Strategic vaccination, semi scavenging practices should be introduced and promoted in order to reduce chicken mortality. Capacity building through training and intensive follow up should also be made in order to enhance the level of awareness of smallholders on improved small scale poultry keeping practices.